174 The EXTEND Trial: EXTENDed Antibiotics to Improve Outcomes in Patients with Complicated Intra-Abdominal Infection. (19th August 2022) - O'Connor, Olivia; Kirby, Andrew; Ahmed, Shadia; Harmston, Rebecca; Hewitt, Catherine; Knowlson, Catherine; Pinkney, Thomas; Szakmany, Tamas; Tharmanathan, Puvan; Vargas-Palacios, Armando; Welch, Charlie; Burke, Dermot
Abstract: Introduction: Complicated intra-abdominal infections (cIAI) pose a major challenge in surgical patients. Despite the heterogenous aetiology they have a common disease process, which is bacterial infection of the peritoneal space. Hence, all cIAIs are managed with source control, plus antibiotic therapy. However, there is uncertainty regarding the optimal antibiotic treatment strategy in order to prevent relapse or extra-abdominal spread of infection1. At present, there is no UK guidance on the management of cIAIs2. For other serious infections outside the abdomen microbiologists often advise at least 28-days of antibiotic therapy. Currently the effectiveness of extended duration antibiotics in patients with cIAI is unknown. This trial aims to compare the clinical and cost effectiveness of 28-day duration antibiotics with standard care with respect to rate of treatment failure in patients with cIAIs. Secondary outcomes include complications and quality of life. Trial Design: A multicentre, open label, two-arm, parallel group, pragmatic, randomised controlled trial with internal pilot. 1166 consenting adult patients with cIAI will be recruited over 3 years and randomised on a 1:1 basis between 28-days antibiotic course and standard care antibiotics, based on local protocol and clinical assessment. Patients will be recruited from ICUs and hospital in-patient wards across 30 sites. Trial management and funding: EXTEND is sponsored by University of Leeds, hosted by York Trials Unit and funded by NIHR. The Trial Management Group will oversee design and running of the trial. Each site will have a Principal Investigator (PI) with local responsibility. The NIHR Associate PI scheme will enable trainees to participate in the trial.